Mekanisme koping dan Tingkat Stres pada Pasien Hipertensi - Mad Zaini; Saputri, Aditya Budi; Arifinda, Putri Ayu Budi; Asrofiah, Karisma Faizatul; Aprilia, Anggun (STIKES Ngesti Waluyo, 2022)
Hypertension is defined as a chronic increase in blood pressure. Hypertension is influenced by many factors, such as genetic, gender, age, obesity, salt consumption habits and stress factors. The purpose of this study was to determine the coping mechanisms, stress levels and the correlation between these two variables in patients with hypertension. The design used in this study was a correlation design with a cross sectional approach to a sample of 54 respondents. The sampling technique used in this research was consecutive sampling. The research instruments used were the Jalowiec coping scale and the Depression anxiety stress scale (DASS) questionnaires, and then the data was analyzed using the Spearman rank test. The results showed that all respondents had adaptive coping mechanisms, and most respondents had normal stress levels, as many as 32 respondents (59.3%). Based on the data analysis results, it is known that the correlation coefficient value is -0.572 p value 0.000 <0.005, which means that there is a strong relationship between coping mechanisms and stress levels in hypertension sufferers in Jember Regency. Adaptive coping mechanism can reduce stress levels for people with hypertension. Education about the application of adaptive coping to control stress can be developed into a nursing intervention method for people with hypertension in health facilities, in order to support the treatment process. Future research is expected to develop research with other variables such as the influence of personality, beliefs and self-concept.